2010
DOI: 10.3758/s13423-010-0016-2
|View full text |Cite
|
Sign up to set email alerts
|

Post-conflict slowing: cognitive adaptation after conflict processing

Abstract: The aftereffects of error and conflict (i.e., stimulus or response incongruency) have been extensively studied in the cognitive control literature. Each has been characterized by its own behavioral signature on the following trial. Conflict leads to a reduced congruency effect (Gratton effect), whereas an error leads to increased response time (post-error slowing). The reason for this dissociation has remained unclear. Here, we show that post-conflict slowing is not typically observed because it is masked by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 16 publications
6
85
2
Order By: Relevance
“…Data from a 1,094,886-trial lexical decision task showed that people slow down after an error, and a diffusion model decomposition showed that this slowdown can be attributed almost exclusively to an increase in response caution. This result confirms the traditional explanation of PES in terms of selfregulation and cognitive control (e.g., Botvinick et al, 2001;Cohen et al, 2000;Brewer & Smith, 1989;Fitts, 1966;Hajcak et al, 2003;Li et al, 2006;Rabbitt & Rodgers, 1977;Shiels & Hawk, 2010;Smith & Brewer, 1995;Tops & Boksem, 2010;Verguts, Notebaert, Kunde, & Wühr, 2011;Vickers & Lee, 1998): that is, people adaptively change their response thresholds to a possibly nonstationary environmentby becoming more daring after each correct response, and by becoming more cautious after each error, people reach an optimal state of homeostasis that is characterized by fast responses and few errors.…”
Section: Concluding Commentssupporting
confidence: 74%
“…Data from a 1,094,886-trial lexical decision task showed that people slow down after an error, and a diffusion model decomposition showed that this slowdown can be attributed almost exclusively to an increase in response caution. This result confirms the traditional explanation of PES in terms of selfregulation and cognitive control (e.g., Botvinick et al, 2001;Cohen et al, 2000;Brewer & Smith, 1989;Fitts, 1966;Hajcak et al, 2003;Li et al, 2006;Rabbitt & Rodgers, 1977;Shiels & Hawk, 2010;Smith & Brewer, 1995;Tops & Boksem, 2010;Verguts, Notebaert, Kunde, & Wühr, 2011;Vickers & Lee, 1998): that is, people adaptively change their response thresholds to a possibly nonstationary environmentby becoming more daring after each correct response, and by becoming more cautious after each error, people reach an optimal state of homeostasis that is characterized by fast responses and few errors.…”
Section: Concluding Commentssupporting
confidence: 74%
“…1a). However, such "postconflict slowing" is hard to interpret when the conflict-laden irrelevant stimulus features repeat, as was the case here (see Verguts et al, 2011, for a discussion of this issue). We therefore refrain from an extended discussion of this observation.…”
Section: Discussion Of Experiments 1a and 1bmentioning
confidence: 78%
“…This finding should be viewed with caution, however, first because postconflict slowing is hard to interpret when the taskinterfering features repeat from trial to trial (cf. Verguts et al, 2011), and second because the effect was not replicated in Experiment 3.…”
Section: Discussionmentioning
confidence: 99%
“…The adaptation by binding model explains these adaptation effects by assuming that the continuous exposure to conflicting situations increases the associative learning so connections between relevant units become very strong. As a consequence, the influence of irrelevant units (word input units) decreases and the Stroop effect reduces (see Verguts, Notebaert, Kunde, & Wühr, 2011, for an elaboration on cognitive control, conflict resolution, and adaptation to conflicting situations). On the other hand, the conflict monitoring theory would defend that conflict adaptation would result from the continuous increased attention to the task-relevant units after responding to many conflicting trials.…”
mentioning
confidence: 97%